Retrospective study of pattern of treatment in free health camps from 2005 to 2017 in East Singhbhum, Jharkhand, India - Kumar, Ratan; Rao, Jakka Srinivas; Biswas, Chandan (International Journal of Research in Medical Sciences, 2018)
Background: Free health camp is a common objective of non-governmental organization (NGO). Government health department alone or jointly with NGO use to organize free medical camp for some specific health program. This retrospective study of occurrence and proportion of diseases and their pattern of treatment was done for period from 2005 to 2017 with an NGO has been working in East Singhbhum district of Jharkhand. Methods: The data of patients over the age of 05 years attended the free health camp from 2005 to 2017 and consent were provided by NGO concerned in this study. The year wise, block wise number of patient, male/female ratio and list of drugs used in different time were tabulated for analysis. Results: The result of this study has been noted in four different tables which elaborates the total number of patients year wise, block wise, percentage wise, male/female ratio during thirteen years. Another table showed occurrence of diseases/ailments in different period with changing percentage of use the drugs in their treatment. Conclusions: This retrospective study provides a conception about some changes in occurrence of diseases in free medical camp in the rural areas of Jharkhand in thirteen years. These health camps have tried to provide and follow the treatment according to need of the patients with safer, efficacious, economical drugs and with periodical inclusion of new generation drugs.